Description of Students Thinking on Warshall-Floyd Algorithm - Zaini Zaini (STKIP Singkawang, 2019)
The shortest path continues to be a trend until now that is always discussed and developed. This study focuses on the construction process and description of the students' understanding in deciding the shortest route based on the matrix iteration according to the Floyd-Warshall algorithm. The research approach used is descriptive qualitative research and the data collection technique is a test technique. The research data included problem-solving by four students with different abilities and the result data were analyzed inductively. The results showed that the matrix iteration with the formula for determining the entry of the iteration matrix xn = minimum(dijk-1, dikk-1 + dkjk-1) was followed without any constraints by all students until the 7th iteration. It was found that the inaccuracy of taking entries in the 1st iteration by students with low ability caused calculation errors and failure in finding the shortest route.